IJSMIEN 2023
DOI: 10.58599/ijsmien.2023.1205
|View full text |Cite
|
Sign up to set email alerts
|

Text Classification using Incremental Learning for many classes of Support Vector Machines

Abstract: This study introduces class-incremental learning (CIL). This framework improves multi-class data support vector machines (SVMs). CIL is incremental feature selection and training. Both steps update SVM classifiers as new classes are added to a system. CIL learns one binary sub-classifier and reuses classifier models for subsequent classes. Another feature selection stage follows. Testing applies the classifier to subspacerelevant vector projections. The CIL system is compatible with any binary classification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The proposed approach achieved the state-of-the-art results with comparison of other machine learning algorithms. We also experimented with other machine learning algorithms such as RF [18], Naïve Bayes [19], LR [20], and SVM [21] along with TF-IDF [22] word embedding technique. We found that our proposed approach is performing well in all seven different categories.…”
Section: Experimental Setup Results and Insightsmentioning
confidence: 99%
“…The proposed approach achieved the state-of-the-art results with comparison of other machine learning algorithms. We also experimented with other machine learning algorithms such as RF [18], Naïve Bayes [19], LR [20], and SVM [21] along with TF-IDF [22] word embedding technique. We found that our proposed approach is performing well in all seven different categories.…”
Section: Experimental Setup Results and Insightsmentioning
confidence: 99%